ANALISIS TREND PENINGKATAN JUMLAH KUNJUNGAN PASIEN DITINJAU DARI MARKETING MIX - Ratna Wardani (Fakultas Kesehatan Masyarakat, Universitas Jember, 2015)
Increase in the human population and the state of the economy more advanced, giving impact public awareness of health increase. Increasing visitors in the hospital, so the hospital have to increase the facilities to existing and improve the quality of services given. These are aiming that the patients will be served rapidly and well. Purpose of this research is to analyze increasing trend the number of patient visits in terms of marketing mix done Hospital HVA Toeloengredjo, Pare. This research using design descriptive research by analysis time series using moving average with a model ARIMA. Observational research methodology, with the subject is the medical record and marketing officer, as well as its object is the data on thenumber of patient visits new and old patient. The results of testing model got that model ARIMA (1,1,0) is a model that can be used to do a forecast or estimate of. The prediction of visitors keeps increasing, where predictions the number of visits all patients during 60th month (December 2016) is 10746 visits, the prediction of the number of patient visits new is 1660 visits, the prediction of the number of patient visits long been 9290 visits. With the results of the number of a prediction patient visits that rises this, is expected to help hospital for prepared an increase in-patient room facilities, free wifi in waiting room to add comfort visitors, prime service, the addition of medical equipment, extension worker medical or so far and also resources support to create customers satisfied who come to the Hospital HVA Toeloengredjo, Pare.Keywords : Marketing Mix, Time Series, Visit